The effect of capsaicin derivatives on tight-junction integrity and permeability of Madin-Darby Canine Kidney cells - Kaiser, Mathias; Gorzelanny, Christian (Journal of pharmaceutical sciences, 2016)
Capsaicin is known to interfere with tight junctions (TJs) of epithelial cells and therefore to enhance paracellular permeability of poorly absorbable drugs. However, due to its low water solubility, pungency, and cytotoxicity, its pharmacologic use is limited. In this study, we investigated the effect of capsaicin derivatives of synthetic (e.g., 10-hydroxy-N-(4-hydroxy-3-methoxybenzyl)decanamide, etc.) and natural (olvanil and dihydrocapsaicin) origin on Madin-Darby Canine Kidney-C7 cells. Impedance spectroscopy was used to determine the transepithelial electrical resistance and the capacitance. Permeability assays with fluorescein isothiocyanate-dextran were carried out to evaluate the impact on cell permeability. The results show that lipophilicity could play an important role for the interference with TJ and that the mechanism is independent from the ion channel TRPV-1 and hence on the flux of calcium into the cells. In summary, we synthesized 4 derivatives of capsaicin of lower lipophilicity and compared their properties with other well-known vanilloids. We show that these compounds are able to enhance the permeability of a hydrophilic macromolecule, by opening the TJ for a shorter time than capsaicin. This behavior is dependent on the lipophilicity of the molecule. Understanding of these phenomena may lead to better control of administration of therapeutic molecules.
Gesehen am 29.01.2019